Implementation of Pancasila Students Profile through Establishment Values of Indonesian Folktale in Madrasah Ibtidaiyah - Rosa Dewi; Gamayanti Novi Rahmawati; Jauharoti Alfin; Nasiri Nasiri (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
Adolescence is a time when a person is in search of identity, trying to get to know who he really is. because they often get figures or role models from television shows and commercial films as well as youth social media which often imitate styles, languages, foreign cultures so that it can lead to a lack of love for the nation's wealth. By implementing the values ​​that exist in folklore, it aims to instill values ​​and attitudes, as well as changes in behavior that occur after the instillation of values ​​and national character education. Folklore contains: 1) presenting the best characters, and 2) ideal figures for youth role models, becoming a representation and picture of social reality, including local wisdom and the social reality of the Indonesian people. Folklore can process the psychology and emotions of the reader. Dramatized plots, interesting storylines, giving surprises and curiosity, characterizations with firm characteristics, language that is easy to digest. This research uses qualitative research to prove that in Indonesian folklore there is the concept of Pancasila students increasing students' reading motivation. , emphasizing student activity and learning outcomes.